2016
DOI: 10.1016/j.tcb.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Filling the Void: Proximity-Based Labeling of Proteins in Living Cells

Abstract: There are inherent limitations with traditional methods to study protein behavior or to determine the constituency of proteins in discrete subcellular compartments. In response to these limitations, several methods have recently been developed that use proximity-dependent labeling. By fusing proteins to enzymes that generate reactive molecules, most commonly biotin, proximate proteins are covalently labeled to enable their isolation and identification. In this review, we describe current methods for proximity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
216
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(231 citation statements)
references
References 94 publications
(67 reference statements)
0
216
0
3
Order By: Relevance
“…Proximity labeling provides a means to capture the immediate biochemical environment of a protein as it exists in situ, thus preserving the critical spatial and temporal context (Kim and Roux, 2016). Various methods have been developed but, among them, engineered ascorbic acid peroxidase (APEX) is of particular interest because of its rapid labeling kinetics (Lam et al, 2015; Martell et al, 2012; Rhee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Proximity labeling provides a means to capture the immediate biochemical environment of a protein as it exists in situ, thus preserving the critical spatial and temporal context (Kim and Roux, 2016). Various methods have been developed but, among them, engineered ascorbic acid peroxidase (APEX) is of particular interest because of its rapid labeling kinetics (Lam et al, 2015; Martell et al, 2012; Rhee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme-mediated ligation methods can be used for several distinct purposes including building peptide/protein assemblies (1,2), making site-specific protein modifications (3,4), and elucidating protein-protein interactions (PPIs) (see (5) for review). Proteins regularly form complex and specific networks critical to the structural and functional integrity of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Since its development and initial application in 2012 (7), BioID has been cited and/or applied in over 200 PubMed-published articles and has been utilized in several unicellular organisms (see (1215) for examples), mammalian cells (5), plants (16,17), and mice (1820), including compartmental proteomics of a parasitic organism infecting mice (21). Novel or improved applications using BioID ligase have spurred numerous follow-up articles including a smaller version of BioID with improved sensitivity and localization (22), its use for identifying protein-RNA interactions (23), split-BioID studies (24,25), and faster versions of BioID (26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1A). This proximal biotinylation has been successfully used to identify novel protein interactions [see reviews: 4, 9], and has been shown as complementary to traditional affinity purification approaches [10]. Interests in this approach have led to improved variants of BioID proteins: BioID2, a smaller biotin ligase from Aquifex aeolicus [11], and a split-BioID as a dimerization dependent biotin ligase [12, 13].…”
Section: Introductionmentioning
confidence: 99%